Burnout dimensions and associated risk factors in medical students: A cross-sectional study in Serbia - Irena Ilic; Ivana Zivanovic Macuzic; Milena Ilic; Ana Ravic-Nikolic; Vesna Milicic (PLoS ONE, 2026)
Introduction Burnout syndrome presents a serious problem for medical students in their training and professional career. The aim of this study was to investigate the dimensions of burnout syndrome and associated risk factors among medical students in Serbia. Methods This was a cross-sectional study. Prevalence of high risk of burnout in medical students was determined following the three-dimensional criteria, based on high levels of emotional exhaustion, cynicism, and low academic efficacy, according to the Maslach Burnout Inventory Student Survey. Odds ratios (OR) with corresponding 95% confidence intervals (95% CI) were determined using multivariate logistic regression analysis. Results Risk for high level of all three burnout dimensions (emotional exhaustion, cynicism, and academic inefficacy) was increasing with higher frequency of alcohol consumption (p for trend = 0.008, p = 0.030, p = 0.040, respectively) in medical students. Risk for high level of emotional exhaustion was associated with clinical training level of studies (OR = 1.82, 95% CI = 1.38–2.80, p = .007) and use of sedatives (OR = 3.08, 95% CI = 1.29–7.38, p = 0.011). Length of study >6 years and use of sedatives were associated with high level of cynicism in medical students (OR = 1.98, 95% CI = 1.08–3.62, p = 0.027; OR = 3.19, 95% CI = 1.31–7.75, p = 0.010, respectively). Higher grade point average (>8) was most common in medical students with lower risk of academic inefficacy (OR = 0.65, 95%CI = 0.44–0.95, p = 0.026). Positive personal medical history (presence of any chronic disease) was frequently reported in medical students who had a high risk of academic inefficacy (OR = 2.45, 95% CI = 1.30–4.61, p = 0.006). Conclusion Some characteristics of medical students were associated with high risk of burnout, indicating the need for psychological support aimed at providing appropriate help and assistance to medical students.